2010
DOI: 10.1155/2010/676351
|View full text |Cite
|
Sign up to set email alerts
|

A Hope Intervention Compared to Friendly Visitors as a Technique to Reduce Depression among Older Nursing Home Residents

Abstract: Depression is common among older persons. An experimental study was undertaken to test the impact of a four-week hope program on depressed nursing home residents. Residents aged 65 or older, who met the criteria for this pilot study and agreed to participate, were randomly assigned to (a) an intervention group, and provided with weekday hope interventions mainly involving positive messages and pictures or (b) a modified control group, and provided with a friendly weekday greeting. The structured hope intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Findings revealed that the group-based hope intervention had a significant and better effect in lowering depression level. This is in line with the previous research where group-based hope intervention had been proven effective to reduce the level of depression of survivors of Merapi volcanic eruption (Retnowati et al, 2015), hemodialysis patients (Rahimipour et al, 2015), mothers of cancer survivors (Shekarabi-Ahari et al, 2012), nurses in nursing homes (Wilson et al, 2010), and elderlies in nursing homes (Farzadegan et al, 2016). This study also shows the hope intervention process influenced depressive symptoms varying from each domain, namely cognitive, affective, and somatic, through a process of self-understanding to recognize problems, strengths, and weaknesses so that they can change negative views of that was believed (Fitriana & Hadjam, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Findings revealed that the group-based hope intervention had a significant and better effect in lowering depression level. This is in line with the previous research where group-based hope intervention had been proven effective to reduce the level of depression of survivors of Merapi volcanic eruption (Retnowati et al, 2015), hemodialysis patients (Rahimipour et al, 2015), mothers of cancer survivors (Shekarabi-Ahari et al, 2012), nurses in nursing homes (Wilson et al, 2010), and elderlies in nursing homes (Farzadegan et al, 2016). This study also shows the hope intervention process influenced depressive symptoms varying from each domain, namely cognitive, affective, and somatic, through a process of self-understanding to recognize problems, strengths, and weaknesses so that they can change negative views of that was believed (Fitriana & Hadjam, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Hope therapy helps people to consider and categorize definite goals, select various ways to achieve their goals, identify barriers and consider related challenges to be overcome ( Clarke, 2003 ; Irving et al, 1997 ; Wilson et al, 2010 ; Chang & Disimone, 2001 ). Su, Tsann-Juu and Yueh-Chih Chen (2006) stated that hope was one of the main effective factors in successful IVF.…”
Section: Discussionmentioning
confidence: 99%
“…Hope is defined as a human strength manifested in the capacities to (a) set specific goals with appropriate difficulty level (goal), (b) develop several specific strategies to attain a goal (pathway), and (c) mobilize and maintain the motivation in goal pursuit process (agency; Snyder, 1994). Using the key word of ''hope intervention'' or ''hope therapy'' to search in PsycINFO from 2000 to 2014, we identified 10 published studies (Berg et al, 2008;Cheavens, Feldman, Gum, Michael, & Snyder, 2006;Duggleby et al, 2007;Feldman & Dreher, 2012;Klausner, Synder, & Cheavens, 2000;MacLeod et al, 2008;RustĂžen, Cooper, & Miaskowski, 2011;RustĂžen & Hanestad, 1998;Wilson et al, 2010). All of the studies adopted Snyder's (1994) definition of hope and designed intervention protocols to improve goal setting and planning skills, foster hopeful thinking, and enhance goal pursuit activities.…”
Section: Hope Intervention Hope Depression and Life Satisfactionmentioning
confidence: 99%